Portugal: Left-wing single-party governments and right-wing coalitions - Calca, P. (Coalition governance in western Europe, 2021)
How have Portuguese political parties, especially the ones in coalition governments, operated? The main focus of this chapter is the study of coalition governments in Portugal since the 2000s. This chapter shows how the country’s governments have shifted back and forth from left-wing single-party governments to right-wing coalition governments during this period. It aims to improve the understanding of Portuguese governments by shedding light on their specificities and dynamics. It is thus useful as a standalone chapter or as a source for multi-country comparisons. The chapter is initiated with a brief description of Portugal’s institutional setting. It is developed further by delving into the country’s party system followed by a discussion of government-formation issues. In conclusion, the chapter considers all the previous information going deeper into coalition governance mechanisms.